Comparative transcriptome analysis of MDBK cells reveals that BoIFN-γ augmented host immune responses to bovine herpesvirus 1 infection - Jiang, Bo; Wang, Jing; Liu, Wenxiao; Cheng, Jing; Xu, Jian; Cao, Mengyao; Li, Yongqing (Frontiers in Microbiology, 2022)
Bovine herpesvirus 1 (BoHV-1) is an alphaherpesvirus that causes infectious bovine rhinotracheitis and infectious pustular vulvovaginitis in cattle. Ιnterferon-gamma (IFN-γ) is a pleiotropic cytokine with antiviral activity that modulates the innate and adaptive immune responses. In this study, we prepared high-purity bovine interferon gamma (BoIFN-γ) dimer protein using prokaryotic expression system and affinity chromatography. We subsequently investigated the effect of BoIFN-γ on BoHV-1 infection in Madin-Darby bovine kidney (MDBK) cells. The results showed that BoIFN-γ pre-treament not only decreased the production of BoHV-1 but also reduced the cytopathic effect of the virus. Differential gene expression profiles of BoHV-1 infected MDBK cells were then analysed through high-throughput RNA sequencing. The data showed that BoIFN-γ pre-treatment reduced lipid metabolism disorder and DNA damage caused by BoHV-1 infection. Furthermore, BoIFN-γ treatment upregulated the transcription of interferon regulatory transcription factors (IRF1 and GBP5) and interferon-stimulated genes (ISGs) of MDBK cells. Additionally, BoIFN-γ promotes expression of cellular protein involved in complement activation and coagulation cascades response as well as antigen processing and presentation process, while BoHV-1 infection dramatically downregulates transcription of these immune components including C3, C1r, C1s, PLAT, ITGB2, PROCR, BoLA, CD74, B2M, PA28, BoLA-DRA, and TAPBP. Collectively, our findings revealed that BoIFN-γ pre-treatment can improve host resistance to BoHV-1 infection and regulate transcription or expression of host protein associated with cellular metabolism and innate immune response. This provides insights into the development of prophylactic agents for prevention and control of BoHV-1 infection.